Agroforestry Harvesting Residue: A Case Study in Private Forests in Probolinggo, East Java, Indonesia - Budiaman, Ahmad; Hardjanto; Ilham, Qori Pebrian; Maharani, Chandra Puspita (Jurnal Sylva Lestari, 2024)
One of the wood sources in Indonesia is derived from private forests managed with agroforestry systems. The harvesting operation in these forests will produce harvesting residues. The study aimed to quantify the harvesting residue volume and to construct a prediction model for harvesting residue volume in a private forest managed with an agroforestry system. The study was conducted in a private forest managed with an agroforestry system in Probolinggo, East Java. The method employed for quantifying harvesting residue was a whole-tree method. The harvesting residue was classified into stumps, butt ends, top logs, and branches. Harvesting residues with dbh >= 4 cm were measured after harvesting. The best model was selected based on the Root Mean Squared Error and the adjusted coefficient of determination values.   The number of sample trees was 31 trees, which were chosen by farmers to be felled. The study found that the harvesting residues were 6% of the total harvested volume. The harvesting residue was predominantly the stumps. The best model for estimating harvesting residue volume in agroforestry private forests was V = 0.042VolTot1.248. The study concluded that harvesting operations in private forests managed with agroforestry systems produced a small number of harvesting residues. The harvested volume was the most significant indicator for estimating the harvesting residue volume.     Keywords: agroforestry, harvesting residue, private forests, predicting models